The infectious salmon anemia virus esterase prunes erythrocyte surfaces in infected Atlantic salmon and exposes terminal sialic acids to lectin recognition - Fosse, Johanna Hol; Andresen, Adriana Magalhaes Santos; Ploss, Frieda Betty; Weli, Simon Chioma; Heffernan, Inger Austrheim; Sapkota, Subash; Lundgård, Krister; Kuiper, Raoul Valentin; Solhaug, Anita; Falk, Knut (Frontiers in Immunology, 2023)
Many sialic acid-binding viruses express a receptor-destroying enzyme (RDE) that removes the virus-targeted receptor and limits viral interactions with the host cell surface. Despite a growing appreciation of how the viral RDE promotes viral fitness, little is known about its direct effects on the host. Infectious salmon anaemia virus (ISAV) attaches to 4 O-acetylated sialic acids on Atlantic salmon epithelial, endothelial, and red blood cell surfaces. ISAV receptor binding and destruction are effectuated by the same molecule, the haemagglutinin esterase (HE). We recently discovered a global loss of vascular 4-O-acetylated sialic acids in ISAV-infected fish. The loss correlated with the expression of viral proteins, giving rise to the hypothesis that it was mediated by the HE. Here, we report that the ISAV receptor is also progressively lost from circulating erythrocytes in infected fish. Furthermore, salmon erythrocytes exposed to ISAV ex vivo lost their capacity to bind new ISAV particles. The loss of ISAV binding was not associated with receptor saturation. Moreover, upon loss of the ISAV receptor, erythrocyte surfaces became more available to the lectin wheat germ agglutinin, suggesting a potential to alter interactions with endogenous lectins of similar specificity. The pruning of erythrocyte surfaces was inhibited by an antibody that prevented ISAV attachment. Furthermore, recombinant HE, but not an esterase-silenced mutant, was sufficient to induce the observed surface modulation. This links the ISAV-induced erythrocyte modulation to the hydrolytic activity of the HE and shows that the observed effects are not mediated by endogenous esterases. Our findings are the first to directly link a viral RDE to extensive cell surface modulation in infected individuals. This raises the questions of whether other sialic acid-binding viruses that express RDEs affect host cells to a similar extent, and if such RDE-mediated cell surface modulation influences host biological functions with relevance to viral disease.